Analisis Kinerja Keuangan Perusahaan Pertambangan Batu Bara Pada Laporan Tahun Buku 2019-2022 Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus: PT. Bukit Asam Tbk, PT. Indika Energy Tbk, Dan PT Golden Energy Mines Tbk) - Yulfiswandi Yulfiswandi; Yudhistira Yudhistira; Irvan Kurniawan; M.Aidil Basri; Miftahul Jannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purposeoof thisoresearch is to determineohow corporate socialoresponsibility (CSR) significantly affects the financialoperformance of coalomining companiesolisted on the IndonesiaiStock Exchange from 2019 to 2022. PT. BukitoAsam Tbk, PT. Indika Energy Tbk, and PT GoldenoEnergy Mines Tbk have provided data for this research. This study adopts a quantitative approach. The Indonesian Stock Exchange gallery serves as the data source for this research. Secondary data obtained from the companies' annualoreports are utilized. Data collection and documentation methods can be found on the Indonesian Stock Exchange website (https://idx.co.id/en). The research indicates that corporateosocial responsibilityodoes not significantly impact the financialoperformance of the companies. In other words, corporate social responsibility does not influence Return onoAssets (ROA) or Return onoEquity (ROE). Keywords: Financial Performance, ROA, ROE, Mining, Coal